Case Study : Mastuki Supplier Trading / Farah Hanisah Ibrahim - Ibrahim, Farah Hanisah (2020)
This project has been done to help students to improve their entrepreneurship skill and student can apply technology solution in real life. To complete this case study, we got an opportunity to interview the owner of the Mastuki Supplier Trading. Mastuki Supplier Trading is a supplier company that supply various types of chips and ‘kuih raya’. Other than that, they also produce spicy cassava chips as their main production of this company. Mastuki Supplier Trading located at Batu Pahat, Johor. In this case study, we need to ask about the problem that faced by the company, analyse the problem and find solution for the company. SWOT analysis have been chosen to complete our report. While gathering the information by using SWOT analysis, we were able to identify the strengths, weakness, opportunities and threats of the company. Based on this analysis, we found a few problems that faced by Mastuki Supplier Trading such as take longer period to pack their product, the location of the company is not strategic and there are many competitors that need to compete. To complete this technology entrepreneurship (ENT 600) subject we are required to make an innovation for this company to help them in solve their problems. We found a great technology that can help Mastuki Supplier Trading in production process. Thus, in this report we will explained in detailed about how our technology can help Mastuki Supplier Trading.